Nuove scoperte de'Russi al nord del Mare del Sud sí nell' Asia, che nell' America / Presso Antonio Zatta - Zatta, Antonio, active 1757-1797 (Venezia : Presso Antonio Zatta, 1776)
Is Part Of Zatta, Antonio, active 1757-1797. Atlante novissimo. Venezia, 1775-85 t. 1, no. [15]. Relief shown by hachures.; Conical projection.; Copper engraving is hand-colored.; "[S]hows the western coast of North America from the Baja Peninsula, along the coast of California to Alaska, and thence to the Bering Strait and the Kamchatka Peninsula. The map is filled with hypothetical cartography based on misunderstood or mythical reports about the northern Pacific shores"--Barry Lawrence Ruderman Antique Maps, Inc. website, viewed on October 15, 2015. Wheat, v. 1, no. 167 Lowery no. 584 Bancroft lib., Index to printed maps, supp Michigan U. Clements lib., Cat. of maps Wagner, H.R., The cartography of the northwest coast of America, no. 654 "The idea of a Northwest Passage linking the Hudson Bay to the Pacific is central to this map . embraces the speculative geography advocated by Nicholas De L'Isle and Phillipe Bauche. De L'Isle and Bauche were supporters of the Northwest Passage theory associated with the apocryphal voyage of the 17th century Admiral de Fonte . Both the Kingdom of Anian and the Straight of Anian . Just south of the Strait of Anian, Zatta includes 'Fou-Sang' which he describes as a Chinese Colony. Fusang of Fousang is a region first documented by the Chinese Buddhist missionary Hui Shen in the 5th century. Hui Shen describes a land some 20,000 Chinese Li (c. 8000 km) east of the China coast . In later days Fusang was commonly used in Chinese poetry to designate Japan, however earlier references keep it distinct . Hui Shen's description of Fusang with regard to distance and geography, corresponds more with the coastlands of North America than with Japan. The French historian Joseph de Guignes in his 1761article 'Le Fou-Sang des Chinois est-il l'Amérique? ' promoted this idea. Cartographers of the era, including Zatta, embraced the idea and it was included in many subsequent maps of the region . Traveling eastward from the colony of Fu-sang Zatta has us following the apocryphal River of the ...